The influence of feedback in the simulated patient (SP) case-history training among audiology students at the International Islamic University Malaysia - Dzulkarnain, Ahmad Aidil Arafat; Ahmad Sani, Maryam Kamilah; Rahmat, Sarah; Jusoh, Masnira (The Korean Audiological Society and Korean Otological Society, 2019)
Background and objective: There is scant evidence on the use of simulations in audiology (especially in Malaysia) for case-history taking, although this technique is widely used in training medicine and nursing students. Feedback is one of the important components in simulations training; however, it is unknown if feedback by instructors could influence the simulated patient (SP) training outcome for case-history taking among audiology students. The aim of the present study is to determine whether the SP training with feedback in addition to the standard role-play and seminar training is an effective learning tool for audiology case-history taking. Subjects: Twenty-six, second-year undergraduate audiology students participated Methods: A cross-over study design was used. All students initially attended two hours of seminar and role-play sessions. Students were then divided into three types of training, (i) SP training (Group A), (ii) SP with feedback (Group B) and, (iii) a non-additional training group (Group C). After two training sessions, the students changed their types of training to, (i) Group A and C: SP training with feedback and, (ii) Group B: non-additional training. All the groups were assessed at three points: (i) pre-test, (ii) intermediate, and (iii) post-test. The normalized median score differences between and within the respective groups were analysed using non-parametric tests at 95% confidence intervals. Results: Groups with additional SP trainings (with and without feedback) showed a significantly higher normalized gain score than those without any additional training (p<0.05). Conclusions: SP training (with/without feedback) is a beneficial learning tool for history taking for audiology students.